Life Satisfaction of International Students: (How) Do Study Demands, Institutional, and Individual Resources Matter? - Juan Serrano-Sánchez; Julia Zimmermann; Edgar Hahn; Dina Kuhlee (Education Sciences, 2025)
International students are an important group at German higher education institutions. Yet few studies have considered the psychosocial situation of these students. The present study combines the study demands-resources model (SD-R model) and the acculturation framework to adapt the former to the specific situation of international students, and examines the effects of study demands, institutional resources, individual resources (acculturation orientations, i.e., affective and cognitive orientations towards the home and host country), stress, and engagement on their life satisfaction as one indicator of well-being. We used cross-sectional survey data from 503 international students across more than 20 higher education institutions. Latent structural equation models showed that lower study demands were associated with lower stress and higher student engagement, which in turn predicted greater life satisfaction. Although higher institutional resources also related to increased engagement and, thus, higher life satisfaction, they were unexpectedly linked to increased stress, which was in turn associated with lower life satisfaction. Additionally, the expected positive effect of affective host country orientation on life satisfaction, mediated through perceived stress and engagement, was confirmed. The consideration of acculturation orientations in the SD-R model helps to understand the specific conditions of well-being amongst international students in Germany.